High similarity and high frequency of virulence genes among Salmonella Dublin strains isolated over a 33-year period in Brazil - Vilela, Felipe Pinheiro (Braz J Microbiol, 2019)
Salmonella Dublin is a strongly adapted serovar that causes enteritis and/or systemic disease with high rates of mortality in cattle and occasionally infects humans. Despite the importance of this serovar, there is a lack of studies in Brazil. The aim of this study was to characterize the genetic diversity of 112 S. Dublin strains isolated from humans and animals in Brazil by CRISPR and CRISPR-MVLST and the relatedness among strains by MLST. In addition, the frequency of some important virulence genes was verified. The strains studied belonged to nine different sequence types, being all of them single- or double-locus variants of the ST10. CRISPR discriminated the strains into 69 subtypes with a similarity ≥ 84.4% and CRISPR-MVLST into 72 subtypes with a similarity ≥ 84.7%. The virulence genes ratB, lpfA, mgtC, avrA, sopB, sopE2, sifA, sseA, ssrA, csgA, fliC, and sinH were found in all the strains studied, while spvB, spvC, sodCl, rpoS, sipA, sipD, invA, and hilA were detected in ≥ 93.7% of the strains. In conclusion, the high similarity among the strains reinforces the clonal nature of the strains of this serovar that may have descended from a common ancestor that little differed over 33 years in Brazil. CRISPR and CRISPR-MVLST showed to be good alternatives to type S. Dublin strains. MLST suggested that S. Dublin strains from Brazil were phylogenetically related to strains from other parts of the globe. Moreover, the high frequency of virulence genes among the strains studied reinforces the capacity of S. Dublin to cause invasive diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s42770-019-00156-5) contains supplementary material, which is available to authorized users.